2004
DOI: 10.1111/j.1365-2648.2004.03262.x
|View full text |Cite
|
Sign up to set email alerts
|

Women's experiences of bulimia nervosa

Abstract: Understanding the experience of bulimia for women who suffer from this disorder is important. Bulimia often presents as a chronic and potentially lifelong health issue. Awareness of bulimic women's perspectives could promote a comprehensive appreciation of bulimia, its aetiology, and directions for treatment alternatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 27 publications
3
49
0
3
Order By: Relevance
“…70 A qualitative study of 13 women with BN analyzed interviews about their experiences and found the most prominent theme to be isolating the self, which included such behaviors as concealing eating and sneaking food. 71 A limitation of these studies is that they did not measure embarrassment and eating alone …”
Section: Additional Criteriamentioning
confidence: 99%
“…70 A qualitative study of 13 women with BN analyzed interviews about their experiences and found the most prominent theme to be isolating the self, which included such behaviors as concealing eating and sneaking food. 71 A limitation of these studies is that they did not measure embarrassment and eating alone …”
Section: Additional Criteriamentioning
confidence: 99%
“…Desde esta perspectiva se interpretó y analizó la experiencia de la enfermedad en familiares de enfermos terminales de cáncer. Es una mirada desde la cual se han realizado diversos estudios en el área de la salud -en enfermería, medicina, trabajo social, entre otras-, que se han enfocado en identificar la vivencia o experiencia de las personas respecto del dolor, la enfermedad, los cuidados en los servicios de salud, la relación de profesionales de la salud con pacientes y familiares, entre otros (10,11,8,(12)(13)(14)(15).…”
Section: Tipo De Investigaciónunclassified
“…I've got to accept that I've done it and then block it out as if I haven't done it or else I will dwell on it Kelly does not understand her recovery as a reduction of eating disorder symptoms but rather in terms of management and acceptance. Instead of suffering the debilitating guilt commonly associated with a binge-purge episode (Broussard, 2005), Kelly is able to "block it out". Rather than punishing herself and slipping "further down" in her mood she is able to move on.…”
Section: Third Set Of Interviewsmentioning
confidence: 99%